Beberapa Faktor Sosio-Antropologis yang Mendorong Perlunya Reformulasi Pemikiran Hukum dalam Islam - Roibin Roibin (Islamica: Jurnal Studi Keislaman, 2008)
We have moved away from the era of the prophet, the exemplary disciples of the prophet, the founders of the madhhab, and the era of the classical ?ulama. This periodical ?moving away? has a tremendous impact on the way we understand Islam. While the revelation has long been ceased since the passing away of the prophet, our social and cultural problems have at the same time increased and intensified. This requires a serious ijtihad to solve some serious problems facing our society. We are obliged to exercise our utmost intellectual ability to extrapolate what Islam has to say concerning these problems. During the lifetime of the prophet, Muslims could consult him on all issues facing them. Vis-?-vis this, the prophet could always offer a satisfactory answer due to his prudence, intellectual acumen, and indeed divine guidance. Muslims living in the post-prophetic eras have to accept that the prophet is no longer with them. They have to rely on their ability to do the ijtihad by interpreting and reinterpreting the divine texts, articulating the views of the previous ?ulama, and proposing new ideas in line with the spirit of the Qur??n and the prophetic tradition. This paper deals with the complexity of ijtihad in modern time by highlighting the necessity of reformulating the Islamic thought on Divine Law so that the teachings of Islam may stay relevant to the demand of modern man.